Increases in body weight and nutritional status of transplanted Alaskan caribou - Valkenburg, Patrick; Spraker, Ted H.; Hinkes, Michael T.; Van Daele, Lawrence H.; Tobey, Robert W.; Sellers, Richard A. (Rangifer, 2000)
Body weight and natality rate in ungulates can be useful indices to nutririon, bur they may also be influenced by genetic and climatic factors. Because caribou {Rangifer tarandus granti) are distributed as discrete populations of metapopulations (i.e., herds) that are usually reproductively isolated from each other for unknown periods, it is difficult to separate the influence of genetics and nutrition on body weight, especially where historical data are lacking. To help elucidate the influence of nutrition on potential variation in body weight and natality of caribou in Alaska, we reviewed data for body weight and natality in 5 populations which resulted from Transplants to previously ungrazed ranges, or to areas where reindeer and caribou had been absent for many decades. In 2 of 5 populations body weight increased significantly, and likely increased in the other 3 populations, but data were insufficient. Natality rate increased in all 5 populations, proportion of fecund yearlings was high and 3 of the 5 newly established herds increased at about the maximum biological potential for the species (lambda=1.35). In the Adak transplant, a lactating yearling was documented. These 5 transplanted populations provide additional evidence that body weight and natality rate in Alaskan caribou are sensitive to changes in population density and relatively short-term (i.e., 10 years) increases in grazing pressure independenr of climate and genetics.